The Antibiotic Resistance Genes Contamination of Strawberries With the Long-Term Use of Raw, Aerobic Composting, and Anaerobic Composting Livestock Manure: A Comparative Study - Zhang, Wei-Guo; Zhang, Ming-Sha; Li, Wen (Frontiers in Environmental Science, 2022)
Strawberry fruits are easily contaminated with antibiotic resistance genes (ARGs) in the soil fertilized with livestock manure, which is widely used by farmers in order to increased yield and fruit quality. Composting can reduce the ARGs contamination in livestock manure. However, there is a knowledge gap in understanding and comparing the ARGs contamination of strawberries with the long-term use of raw, aerobic composting, and anaerobic composting livestock manure. In this study, our results suggested that compared with the long-term use of raw livestock manure, both aerobic and anaerobic composting livestock manure reduced the ARGs diversity and abundance of strawberries. Mobile genetic elements (MGEs) closely determined the ARGs dissemination. The correlation analysis between ARGs and MGEs revealed the ARGs dissemination from fruits to human was attenuated when strawberries were fertilized with long-term use of composting livestock manure. In addition, this study illustrated the correlations between the antibiotic resistome and microbiome via network co-occurrence analysis, finding that the phylum Proteobacteria, Firmicutes, and Myxococcota were identified as the potential ARGs hosts which exerted the vital role in the environmental behavior of ARGs. The most important highlight was that the contamination of ARGs of strawberries was alleviated by the long-term use of composting livestock manure, especially the anaerobiotic composting manure.